Assessing the Cytotoxicity of Materials Used as Bonding Agents in Orthodontic Fixed Retainers - Javaheripour, Aylar; Shafaei, Hajar; Ghaffarloo, Ilyad; Sohrabi, Aydin (Journal of Dental School, 2024)
Objectives Fixed orthodontic retainers are pivotal in determining the success of treatment outcomes. However, the bonding materials utilized in their construction are not completely inert. These materials may release bisphenol A (BPA), a compound associated with various health risks. This study aimed to evaluate the cytotoxicity of potential bonding agents used in fixed orthodontic retainers. Methods In this experimental study, human gingival fibroblasts were cultured and subjected to various dental materials. These materials included acrylic resin (representing removable retainers), Transbond LR, and Enlight LV (which are common adhesives for fixed retainers), as well as Gradia Direct, Direct Flo, and Herculite XRV (commonly used in restorative composites). A control group was also exposed to normal saline. Discs measuring 0.5×1×1 mm were prepared from these materials. The viability of the fibroblasts was assessed using the MTT assay, and a statistical analysis (one-way analysis of variance) was conducted to compare the groups at a significance level of 0.05. Results The results of statistical analysis indicated no significant difference between the groups in terms of cytotoxicity for human gingival fibroblasts (p= 0.71). Conclusion None of the tested materials negatively impacted the viability of human gingival fibroblasts. These results provide valuable clinical insights, reassuring orthodontic practitioners about the safety profile of these commonly used materials in the context of fixed orthodontic retention and restorative procedures.